Reconciling Colonial Narrative and Contemporary Needs: A Tripartite Adaptive Reuse Strategy for Heritage Conservation in Indonesia - Luthfian Teddya Renanta; Silmi Cahya Pradini Priliana (Faculty Of Arts and Design Sebelas Maret University, 2026)
Gedung Juang 45 in Pati is a cultural heritage building with significant historical value, but currently it faces several challenges such as declining physical condition and spatial functions that no longer meet the needs of contemporary society. This research aims to redesign the interior of the Gedung Juang 45 complex by applying the adaptive reuse approach in order to preserve its historical value while reactivating its role as a relevant public space. The research method uses a qualitative-descriptive approach through field surveys, observation of user activities, and literature study related to strategies for adapting historical buildings. The design strategy focuses on three main interventions: insertion for adding new elements without changing the main structure, intervention for functional modifications while maintaining the building authenticity, and installation for the addition of flexible interior elements. The design results show that the integration of old and new elements through the arrangement of educational, communal, and commercial zoning can improve spatial quality and strengthen community place attachment to local cultural heritage. This study concludes that adaptive reuse is an effective strategy to maintain the sustainability of cultural heritage buildings as a center for social activities and creative economy that remains relevant for contemporary society. Keywords: adaptive reuse, cultural heritage, Gedung Juang 45 Pati, interior design, public space